Analysis of the Effect of Education Fund Budget on Performance Accountability and Transparency in School Fund Management (Cirebon City) - Astuti, Dewi; Sutirman, Irwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of the education budget on performance accountability and transparency in fund management in Cirebon City schools. Using a quantitative approach, this study examines the relationship between education budget allocation and two important aspects in school management, performance accountability and transparency of fund management. Data was collected from school financial reports and surveys conducted among schools and financial managers in schools in Cirebon City. The results of the analysis show that, with a data sample of 14, with 25 total respondents, there is a significant positive correlation between the education budget and performance accountability (r = 1) and transparency of fund management (r = 0.982). These findings confirm that efficient allocation and use of the education budget not only increases accountability for school performance but also strengthens transparency in fund management. Survey responses, which range from 0 (disagree) to 1 (agree) on a rating scale, indicate positive perceptions of existing financial management practices. This study provides empirical evidence about the importance of good education budget management as a tool for improving the quality of education, especially in Cirebon city schools.